2023
DOI: 10.1080/22221751.2023.2187245
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the cellular and molecular variabilities of peripheral immune cells in healthy recipients of BBIBP-CorV inactivated SARS-CoV-2 vaccine by single-cell RNA sequencing

Abstract: Over 3 billion doses of inactivated vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been administered globally. However, our understanding of the immune cell functional transcription and T cell receptor (TCR)/B cell receptor (BCR) repertoire dynamics following inactivated SARS-CoV-2 vaccination remains poorly understood. Here, we performed single-cell RNA and TCR/BCR sequencing on peripheral blood mononuclear cells at four time points after immunization with the inactivated SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Moreover, there is a strong correlation between the length of H‐CDR3 and IgG1, IgA2, and IgM subtypes following vaccination. Tong et al 62 found the frequency of 18 AA H‐CDR3 and 13 AA L‐CDR3 elevated after the administration of the second dose of BBIBP‐CorV for 14 days. These suggested relatively large differences in the molecular mechanisms of individual B‐cell responses after SARS‐CoV‐2 infection and vaccine administration.…”
Section: Bcr‐cdr3 Features Changes and Significance In Sars‐cov‐2 Inf...mentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, there is a strong correlation between the length of H‐CDR3 and IgG1, IgA2, and IgM subtypes following vaccination. Tong et al 62 found the frequency of 18 AA H‐CDR3 and 13 AA L‐CDR3 elevated after the administration of the second dose of BBIBP‐CorV for 14 days. These suggested relatively large differences in the molecular mechanisms of individual B‐cell responses after SARS‐CoV‐2 infection and vaccine administration.…”
Section: Bcr‐cdr3 Features Changes and Significance In Sars‐cov‐2 Inf...mentioning
confidence: 99%
“…The CSR after SARS‐CoV‐2 vaccination is not completely consistent with that of COVID‐19 patients. Fraley et al 51 found no significant change in isotype proportion after Pfizer‐mRNA vaccination, with no difference between the positive and negative groups; Tong et al 62 discovered that the abundance of IGHA and IGHG increased after the BBIBP‐CorV vaccine administration. Kotagiri et al 42 reported a rise in the proportions of IgD and IgM subtypes, along with a decrease in IgG2, IgA1, and IgE levels following 25 days of BNT162b2 vaccination, while there was a notable increase in IgG1, IgG3, and IgA1 levels following 25 days of TIV vaccination.…”
Section: Bcr‐cdr3 Features Changes and Significance In Sars‐cov‐2 Inf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccine is one of the most cost-effective strategies to cope with the pandemic and reduce mortality with inactivated whole-virus and mRNA vaccines being the most widely deployed vaccine types 2,3 . Despite intensive clinical studies concerning the immunogenicity of vaccines and immunological studies dissecting the immune signaling of vaccineelicited immune response [4][5][6][7][8][9] , we know little about the epigenetic regulatory mechanism of vaccine-elicited immune responses, particularly time-and cell-type-resolved gene regulations that mediate immune responses to SARS-CoV-2 vaccine 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the effectiveness of anti-viral drugs in preventing severe disease and reducing mortality, promoting and popularizing vaccines are the most vital ways to impede virus spread (1,2). Similar to recovered patients with COVID-19, vaccinated subjects (including those vaccinated with mRNA and inactivated SARS-CoV-2 vaccines) displayed an efficient induction of virus-specific T-cell responses and neutralizing antibodies among a wide range of tissues, such as peripheral blood, lymph nodes, and upper respiratory tract mucous (3)(4)(5)(6)(7)(8)(9)(10). This might rationally explain the restrained virus replication, shedding, tissue localization (11), and even the clinically reported decline of severe incidence and mortality after vaccination (4,(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%